New Results of Fixed-Point Theorems in Complete Metric Spaces. (9th August 2022) - Yaseen, Mustafa T.; Ali, Ali Hasan; Al-moneef, Areej A.; Bazighifan, Omer; Nofal, Taher A.; Ghanim, F.
Abstract : In this paper, fixed point theorems of multiple values of self-mappings have been investigated in Banach space. In addition, a new modification of the same mentioned study has been considered in a metric space with at most three valued self-mappings. Moreover, we have extended and improved some existent results in a complete metric space. Finally, we present a slight improvement on some well-known lemmas that are related to nonexpansive mappings and nonincreasing distances mappings.